Elderly Persons With ICU-Acquired Weakness: The Potential Role for β-Hydroxy-β-Methylbutyrate (HMB) Supplementation?. (July 2014) - Rahman, Adam; Wilund, Kenneth; Fitschen, Peter J.; Jeejeebhoy, Khursheed; Agarwala, Ravi; Drover, John W.; Mourtzakis, Marina
Intensive care unit (ICU)–acquired weakness is common and characterized by muscle loss, weakness, and paralysis. It is associated with poor short-term outcomes, including increased mortality, but the consequences of reduced long-term outcomes, including decreased physical function and quality of life, can be just as devastating. ICU-acquired weakness is particularly relevant to elderly patients who are increasingly consuming ICU resources and are at increased risk for ICU-acquired weakness and complications, including mortality. Elderly patients often enter critical illness with reduced muscle mass and function and are also at increased risk for accelerated disuse atrophy with acute illness. Increasingly, intensivists and researchers are focusing on strategies and therapies aimed at improving long-term neuromuscular function. β-Hydroxy-β-methylbutyrate (HMB), an ergogenic supplement, has shown efficacy in elderly patients and certain clinical populations in counteracting muscle loss. The present review discusses ICU-acquired weakness, as well as the unique physiology of muscle loss and skeletal muscle function in elderly patients, and then summarizes the evidence for HMB in elderly patients and in clinical populations. We subsequently postulate on the potential role and strategies in studying HMB in elderly ICU patients to improve muscle mass and function.